Carbapenem Resistance Profiles of Pathogenic Escherichia coli in Uganda - Ssekatawa, Kenneth; Byarugaba, Denis K.; Nakavuma, Jesca L.; Kato, Charles D.; Ejobi, Francis; Tweyongyere, Robert; Wampande, Eddie M. (My University, 2020)
Escherichia coli has been implicated as one of the main etiological agents of diarrhea, urinary tract infections, meningitis and septicemia worldwide. The ability to cause diseases is potentiated by presence of virulence factors. The virulence factors influence the capacity of E. coli to infect and colonize different body systems. Thus, pathogenic E. coli are grouped into DEC strains that are mainly clustered in phylogenetic group B1 and A; ExPEC belonging to A, B2 and D. Coexistence of virulence and beta-lactamase encoding genes complicates treatment outcomes. Therefore, this study aimed at presenting the CR profiles among pathogenic E. coli. Methods: This was a retrospective cross-sectional study involving use of archived E. coli clinical isolates collected in 2019 from four Ugandan tertiary hospitals. The isolates were subjected to antibiotics sensitivity assays to determine phenotypic resistance. Four sets of multiplex PCR were performed to detect CR genes, DEC pathotypes virulent genes, ExPEC PAI and the E. coli phylogenetic groups. Results: Antibiotic susceptibility revealed that all the 421 E. coli isolates used were MDR as they exhibited 100% resistance to more than one of the first-line antibiotics. The study registered phenotypic and genotypic CR prevalence of 22.8% and 33.0% respectively. The most predominant gene was blaOXA-48 with genotypic frequency of 33.0%, then blaVIM(21.0%), blaIMP(16.5%), blaKPC(14.8%) and blaNDM(14.8%). Spearman’s correlation revealed that presence of CR genes was highly associated with phenotypic resistance. Furthermore, of 421 MDR E. coli isolates, 19.7% harboured DEC virulent genes, where EPEC recorded significantly higher prevalence (10.8%) followed by S-ETEC(3.1%), STEC(2.9%), EIEC (2.0%) and L-ETEC(2.0%). Genetic analysis characterized 46.1% of the isolates as ExPEC and only PAI IV536(33.0%) and PAI IICFT073(13.1%) were detected. Phylogenetic group B2 was predominantly detected (41.1%), followed by A(30.2%), B1(21.6%), and D(7.1%). Furthermore, 38.6% and 23.1% of the DEC and ExPEC respectively expressed phenotypic resistance. Conclusion: Our results exhibited significant level of CR carriage among the MDR DEC and ExPEC clinical isolates belonging to phylogenetic groups B1 and B2 respectively. Virulence and CR genetic factors are mainly located on mobile elements. Thus, constitutes a great threat to the healthcare system as it promotes horizontal gene transfer.
Keywords: Carbapenem resistance; Virulence genes; Pathogenicity islands; Pathogenic E